Digital Leadership and its Relationship to Change Management among Female Principals of Public Primary Schools in Riyadh City - Al-Qahtani, Fadaha Saeed; Al-Arifi, Hessh Saad (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of practice of digital leadership dimensions and the nature of the correlation between them among female principals of public elementary schools in Riyadh. The researcher used the descriptive correlational approach and a questionnaire that was distributed to a sample of (307) female principals and teachers. The study reached a number of results, which are: The practice of primary school principals in Riyadh for the dimensions of digital leadership received an overall average of (3.41 out of 5), with a rating of (high), and at the level of dimensions, the level of digital awareness came with an average of (3.44), then digital leadership for administrative work with an average of (3.32), and finally digital human resources with an average of (2.55), while the practice of change management dimensions by principals received an overall average of (3.26 out of 5) with a rating of (average), and its ranking came (the dimension of the school’s relationship with society with an average of (3.36), then the dimension of school leadership with an average of (3.27), and finally the dimension of strategic planning with an average of (3.15). There is a direct relationship of (.84) and reflects a (strong), (positive) relationship between each of the dimensions of digital leadership and the dimensions of change management. Based on the results, the researcher recommended that school principals and teachers use various digital means and applications to accomplish their administrative tasks; in order to build a digital environment in schools through which the dimensions of digital leadership are applied. She also presented proposals for complementary studies in the topic.